Determination of the influence of a stress-relief heat treatment and additively manufactured surface on the fatigue behavior of selectively laser melted AISI 316L by using efficient short-time procedures. (February 2020) - Blinn, Bastian; Krebs, Florian; Ley, Maximilian; Teutsch, Roman; Beck, Tilmann
Graphical abstract: Highlights: Effect of a stress-relief heat treatment (HT) on the fatigue behavior of 316L. Improvement of fatigue strength because of increased defect tolerance after HT. Locally restricted phase transformation at microstructural defects. Significant reduction of fatigue strength due to as-built surface condition. Double-staged S-Nf curves of SLM specimens with as-built surface condition. Abstract: To use Additive Manufacturing (AM) technology for production of safety critical structural components, it is indispensable to investigate thoroughly the materials AM specific microstructure as well as the resulting mechanical and especially cyclic properties. Besides their special microstructure, AM materials show a highly inhomogeneous distribution of residual stresses as well as numerous process induced microstructural notches, e.g. pores in the materials volume and high roughness of additively manufactured surfaces. Therefore, in production of AM components stress-relief heat treatments as well as surface post-processing are commonly used. In the present work, the influence of stress-relief heat treatment as well as the additively manufactured surface condition on the cyclic properties was investigated at selectively laser melted (SLM) specimens made of AISI 316L stainless steel. Specimens were manufactured in horizontal as well as vertical building direction, leading to layer planes oriented parallel and perpendicular to the loading direction, respectively. To reduce the high material and time effort in fatigue investigations, the short-time methods PhyBaLCHT, which is based on cyclic indentation tests and enables a characterization of the materials defect tolerance, as well as load increase tests (LITs) were used for qualitative analyzes of the cyclic deformation behavior. Moreover, the physically based lifetime calculation approach (PhyBaLLIT ) was applied for quantitative determination of the fatigue behavior of heat treated specimens, showing excellent correlation to additional constant amplitude tests (CATs), performed for validation. While the heat treatment does not significantly influence the fatigue behavior of vertically built specimens, an increase of fatigue strength could be observed for horizontal building direction, which is mainly caused by an improved defect tolerance. The higher defect tolerance was determined with PhyBaLCHT and could be proved by fracture mechanics considerations using the area -concept. Furthermore, the results show a significantly lower fatigue lifetime for additively manufactured surface condition compared with polished samples, which is more pronounced for vertically built specimens, because of the higher surface roughness of specimens manufactured in this building direction. Moreover, a double-staged S-Nf curve could be observed for specimens with additively manufactured surface, which correlates to the cyclic deformation behavior observed in LITs and CATs.